WATER CLIMATOLOGICAL BALANCE FOR MUNICIPALITIES OF PIRIPIRI AND SAO JOAO DO PIAUÍ, PIAUÍ, BRAZIL - Ribeiro, A. A.; Simeão, M.; Santos, A. R. B. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The climatic water balance is critical to the availability of water in the soil. Given the above, the present study aimed to prepare the monthly climatic water balance to climate conditions in the municipalities of Piripiri and São João do Piaui, situated in the state of Piaui. The average monthly water balance was drawn from the method developed by THORTHWAITE & MATHER (1955). There were used average monthly data of precipitation and average air temperature the period from 1990 to 2014. The potential evapotranspiration was estimated by Thornthwaite method (1948). It adopted one available water capacity (CAD) average of 100 mm. The municipality of Piripiri, PI presents seven months of water deficit in the soil, reaching 758.7 mm a year, concentrating in the months from june to december. The water surplus totaled 496.1 mm occurring in the months from February to May. The municipality of São João do Piauí, PI shows no month with water surplus. Water stress is concentrated in the months from april to december, with accumulated total of 886.8 mm.